The Benefit of Binaural Hearing Among Listeners with Sensorineural Hearing Loss - PASTUSIAK, Anna; NIEMIEC, Dawid; KOCIŃSKI, Jedrzej; WARZYBOK, Anna (Archives of Acoustics, 2019)
The performance of binaural processing may be disturbed in the presence of hearing loss, especially of sensorineural type. To assess the impact of hearing loss on speech perception in noise regarding binaural processing, series of speech recognition measurements in controlled laboratory conditions were carried out. The spatial conditions were simulated using dummy head recordings played back on headphones. The Intelligibility Level Difference (ILD) was determined by measuring the change in the speech reception thresholds (SRT) between two configurations of a masking signal source (N) and a speech source (S), namely the S0N90 condition (where numbers stand for angles in horizontal plane) and the co-located condition (S0N0). To disentangle the head shadow effect (better ear effect) from binaural processing in the brain, the difference between binaural and monaural S0N90 condition (so-called Binaural Intelligibility Level Difference, BILD) value was calculated.Measurements were performed with a control group of normal-hearing listeners and a group of sensorineural hearing-impaired subjects. In all conditions performance of the hearing-impaired listeners was significantly lower than normal-hearing ones, resulting in higher SRT values (3 dB difference in the S0N0 configuration, 7.6 dB in S0N90 and 5 dB in monaural S0N90). The SRT improvement due to the spatial separation of target and masking signal (ILD) was also higher in the control group (8.1 dB) than in hearing-impaired listeners (3.5 dB). Moreover, a significant deterioration of the binaural processing described by BILD was found in people with sensorineural deficits. This parameter for normal-hearing listeners reached a value of 3 to 6 dB (4.6 dB on average) and decreased more than two times in the hearing-impaired group to 1.9 dB on average (with a deviation of 1.4 dB). These findings could not be explained by individual average hearing threshold (standard in audiological diagnostics) only. The outcomes indicate that there is a contribution of suprathershold deficits and it may be useful to consider binaural SRT measurements in noise in addition to the pure tone audiometry resulting in better diagnostics and hearing aid fitting.